234k views
5 votes
If f(x) = -2x2 - 3 and g(x) = 3x - 4, then f(g(2))=

2 Answers

3 votes

Answer:

If f(x) = -2x2 - 3 and g(x) = 3x - 4, then f(g(2))= f(g(2)) = -11

Explanation:

User Subu Ganesh
by
5.2k points
1 vote

Answer:

f(g(2)) = -11

Explanation:

f(g(2))=

First we need to find g(2)

g(x) = 3x-4

We let x=2

g(2) = 3(2) -4

6-4

=2

Now we stick the value of g(2) in for x in f(x)

f(x) = -2x^2 - 3

f(2) = -2(2)^2 -3

=-2 (4) -3

= -8 -3

=-11

User TantrajJa
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.